Determinants of different modes of FDI : firm-level evidence from Japanese FDI into the US - Wang, Peiming (2013)
There are four major modes through which firms undertake foreign direct investment (FDI) – merger and acquisition (M&A), joint venture (JV), new plant (NP) and others (O). The four modes of FDI are distinct from each other, and each has its own unique advantages and disadvantages. While a large and growing empirical literature examines the determinants of FDI, very few studies examine the determinants of different modes of FDI. The central objective of this paper is to empirically analyze the extent to which the determinants of FDI such as firm size influences the choice of one mode of FDI over another. Our analysis follows a stylized two-stage investment process. First, we look at the probability of whether a Japanese firm is willing to undertake FDI in the US. Second, for firms that are willing to undertake FDI, we analyze which mode of FDI - i.e. M&A, joint venture, new plant or other FDI – they will undertake. The second stage is the innovation of this paper and its contribution to the FDI literature.